1972
DOI: 10.4039/ent1041499-10
|View full text |Cite
|
Sign up to set email alerts
|

PHYSIOLOGICAL INTERACTIONS OF N-SATURATED AND UNSATURATED FATTY ACIDS AND THEIR ESTERS WITH PRE-IMAGINAL STAGES OF AEDES AEGYPTI (DIPTERA: CULICIDAE)

Abstract: Physiological interactions of n-saturated fatty acids, trans-2-unsaturated fatty acids and their methyl and ethyl esters with pre-imaginal stages of Aedes aegypti (L.) have been described. Differences in the response of the larvae and pupae to the same chemical and also the specific interactions of some chemicals synchronized with a short period during the development of a single stage have been emphasized. Investigations of a homologous series of fatty acids and their derivatives indicate that earlier stateme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1972
1972
1974
1974

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Similar abnormalities were also reported when Aedes aegypti (L.) (Spielman and Williams 1966) and Culex pipiens quinquefasciatus Say (Spielman 1970) were treated with this hormone. Abnormal metamorphosis in A. aegypti and Musca domestica L. following treatment with synthetic queen substance analogs, and alkanes and alkenes, were also reported by Quraishi (1971Quraishi ( , 1972a and Thorsteinson (1965a, b and. Similar effects were also noticed with several plant extracts (Quraishi et al 1972).…”
Section: Discussionmentioning
confidence: 52%
“…Similar abnormalities were also reported when Aedes aegypti (L.) (Spielman and Williams 1966) and Culex pipiens quinquefasciatus Say (Spielman 1970) were treated with this hormone. Abnormal metamorphosis in A. aegypti and Musca domestica L. following treatment with synthetic queen substance analogs, and alkanes and alkenes, were also reported by Quraishi (1971Quraishi ( , 1972a and Thorsteinson (1965a, b and. Similar effects were also noticed with several plant extracts (Quraishi et al 1972).…”
Section: Discussionmentioning
confidence: 52%
“…Quraishi and Thorsteinson (1967) reported that Aedes aegypti larvae treated with alkanes or alkenes of chain lengths of 13 carbon atoms or more showed a tendency to hang vertically from the surface of water with their bodies slightly curved, the dorsal surface being convex, whereas the normal larva makes an acute angle with the horizontal with its body held straight. Quraishi (1972) observed that larvae of Aedes aegypti treated with ethyl pentadecanoate and ethyl hexadecanoate exhibited a similar behavior. McFarlane and Henneberry (1965) found that methyl hexadecanoate "drastically" reduced the incidence of wing development.…”
Section: Teratogenic Eflects Of Estersmentioning
confidence: 86%
“…In previous papers (Quraishi 1971 ;Quraishi and Thorsteinson 1965) the effects of saturated and unsaturated fatty acids on larvae of the house fly, Musca domestica L., have been described. Quraishi (1972) also reported upon the physiological interactions of n-saturated and trans-Z-unsaturated fatty acids and their esters with pre-imaginal stages of the yellow fever mosquito, Aedes aegypti L . .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations